2016
DOI: 10.4028/www.scientific.net/amm.852.381
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Wear Analysis of a Metallic Coating on ABS Plastic Substrate

Abstract: In the recent times efforts have been made to combine plastic and metal, and to bring forth a product that has the goodness of both. With metallization the plastic gains the properties like thermal conductivity, strength and hardness. Methods discovered are usually costly, complex and environment unfriendly. Metallization of plastics has opened the door for its use in various fields such as electronic industry, textile industry and automotive industry. Metallic coating are also desirable in providing finish on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Mohamed et al [15] worked on the effects of additive manufacturing parameters on the wear properties of ABS and reported that the wear rate decreased with diminishing layer thickness but with rising in the air gap and raster angle. Nigam et al [16] probed the sliding wear behavior of electric arc sprayed copper-coated ABS substrates. The same research group also simulated the wear mechanism to figure out the probable influences of copper coating layers [17].…”
Section: Introductionmentioning
confidence: 99%
“…Mohamed et al [15] worked on the effects of additive manufacturing parameters on the wear properties of ABS and reported that the wear rate decreased with diminishing layer thickness but with rising in the air gap and raster angle. Nigam et al [16] probed the sliding wear behavior of electric arc sprayed copper-coated ABS substrates. The same research group also simulated the wear mechanism to figure out the probable influences of copper coating layers [17].…”
Section: Introductionmentioning
confidence: 99%